Advances in Hydraulics and Hydroinformatics - Zhou, Jianguo; Zhang, Jianmin; Peng, Yong; Borthwick, Alistair (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue reports on recent research trends in hydraulics, hydrodynamics, and hydroinformatics, and their novel applications in practical engineering. The Issue covers a wide range of topics, including open channel flows, sediment transport dynamics, two-phase flows, flow-induced vibration and water quality. The collected papers provide insight into new developments in physical, mathematical, and numerical modelling of important problems in hydraulics and hydroinformatics, and include demonstrations of the application of such models in water resources engineering.